By the separation of variables technique we write "u(x,y) = \\chi(x)\\phi(y)" therefore we can rewrite or equation as follows :
"\\chi'(x)\\phi(y) + \\chi(x)\\phi'(y) = 2(x+y)\\chi(x)\\phi(y)"
Now we will divide both parts by "u(x,y)=\\chi(x)\\phi(y)" and transfer all functions of a variable x to the left, and these of y to the right:
"\\frac{\\chi'(x)}{\\chi(x)} + \\frac{\\phi'(y)}{\\phi(y)} = 2(x+y)"
"\\frac{\\chi'(x)}{\\chi(x)}-2x = 2y-\\frac{\\phi'(y)}{\\phi(y)}"
On the left we have a function of x only and on the right of y only. Therefore both parts of this equality must be a constant (as x,y are independent) that we will call "\\lambda" . Now let's solve the equations for "\\phi(y), \\chi(x)" :
"\\frac{\\chi'(x)}{\\chi(x)}-2x=\\lambda"
"\\chi'(x) = (2x+\\lambda)\\chi(x)"
"\\chi(x) = A_\\lambda e^{x^2+\\lambda x}"
"2y-\\frac{\\phi'(y)}{\\phi(y)}=\\lambda"
"\\phi'(y) = (2y-\\lambda)\\phi(y)"
"\\phi(y)=B_\\lambda e^{y^2-\\lambda y}"
"u_\\lambda(x,y)=\\phi_\\lambda(y)\\times\\chi_\\lambda(x)=C_\\lambda e^{x^2+y^2+\\lambda(x-y)}"
The range of possible "\\lambda" , the constants "C_\\lambda" are determined by boundary and initial conditions, the general sum can be expressed as a linear (possibly infinite) combination of "u_\\lambda(x,y)" for permitted values of "\\lambda" .
Comments
Leave a comment